Study of microstrip line-fed flower-shaped patch antenna providing enhanced bandwidth and radiation efficiency - Rani Patre S.; Singh S.P. (My University, 2025)
This article presents the simulation and experimental studies of a broadband flower-shaped patch antenna with semi-elliptical partial ground plane fed through tapered microstrip line. The conventional circular patch is reshaped to obtain the proposed broadband flower-shaped patch, which has distinct smaller segments and larger perimeter without changing the (largest) patch radius. The effect of different configurations of feed line and ground plane on the impedance bandwidth of the antenna is studied through simulation using Ansys' High Frequency Structure Simulator (HFSS) software. The simulated and measured bandwidths of the proposed antenna with optimum configurations of feed line and ground plane for input VSWR ≤ 2 are found to be 142% (2.3–13.6 GHz) and 135.88% (2.1–11.0 GHz), respectively. The radiation patterns of the antenna are bidirectional and omni-directional in E- and H-plane respectively. The proposed antenna has high radiation efficiency of more than 80% and reasonable gain over whole operating frequency band. Further, the input and radiation characteristics of the proposed antenna are compared with the respective characteristics of identical antenna excited using coplanar waveguide (CPW) feed. The bandwidth improvement of proposed antenna compared to reference one is explained using leaky wave concept. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2041–2046, 2016. © 2016 Wiley Periodicals, Inc.